MOTIVATION AND AFFECTIVE PRINCIPLE IN LANGUAGE LEARNING: IMPLICATIONS TO EFL LEARNERS AND TEACHERS - Gunas, Tobias (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
Abstract: Motivation and Affective Principle in Language Learning:  Implications to EFL  Learners and Teachers. Teaching and learning language are essentially interrelated with the factor of motivation and affective principle. Many researches have revealed that motivation factor and affective principle have contributed to the success of  language learning. In this case, the effect of motivation and affective principle prove to be of importance for learners in the course of  language learning. This  article is mainly intended to explore  the concept of motivation, affective principle, types of motivation, and motivational strategies as well as implications. Key words: motivation, motivating, and affective principle                                       Abstrak: Motivasi dan Prinsip Afeksi Dalam Pembelajaran Bahasa: Implikasinya pada Pembelajar dan Pebelajar Bahasa Inggris.  Pembelajaran bahasa pada hakekatnya berkaitan erat dengan faktor motivasi dan prinsip afeksi. Berbagai kajian mengungkapkan bahwa faktor motivasi dan prinsip afeksi berpengaruh terhadap keberhasilan pembelajaran bahasa. Dalam hal ini, efek motivasi dan prinsip afeksi terbukti penting dalam pembelajaran bahasa. Artikel ini bertujuan untuk mengkaji konsep motivasi, prinsip afeksi, jenis-jenis motivasi, dan strategi serta implikasinya. Kata kunci: motivasi, memotivasi, dan prinsip afeksi